Solubility of Rock Phosphate and SP-36 in Peat Soils Amended with Mineral Soil - WIWIK HARTATIK; K IDRIS (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2008)
Rock phosphates application on peat soil has a good prospect because of its high solubility in acid condition. However, the study of the solubility of rock phosphate in peat soils is still limited. This study aimed to quantify the solubility of rock phosphate and the effects of some sources of rock phosphates and SP-36 in the peat soils, taken from South Sumatera amended with mineral soil. The study was conducted in the laboratory ofIndonesian Soil Research Institute, in Bogor. The study consisted of two activities: 1) study on the solubility of some rock phosphates (Marocco, Christmas, and Ciamis) in peat soils. For this study a 100 g of oven dried (105oC) peat soil for each treatment was used for this study. The treatments were eleven levels of P i.e. 0, 10, 20, 30, 40, 50, 60, 75, 100, 125, and 150 ppm P applied to dried peat soils. The treated peat soils werethen incubated for 2 weeks before analyses of soluble P was conducted. The molybdat blue method was used to analyze the samples at 2, 4, 8, and 12 weeks after the incubation. 2) The second study i.e. the application of some rock phosphates or SP-36 on the peat soils amended with mineral soils, four levels of P (25, 50, 74, and 100% of P sorption) plus partial and complete control treatments have been replicated twice. Two hundred grams of oven dried peat soils (105oC) amended with mineral soils at 7,5% maximum Fe sorption, incubated for four weeks, and then soluble P was analyzed using molybdat blue at 1, 2, 4, 6, 8, 10, and 12 weeks after incubation. The results showed that the order of rock phosphates solubility in peat soils was Marocco> Ciamis>Christmas. The solubility of P in peat soils amended with mineral soil and rock phosphates gave similarresults as rock phosphate was in the order of SP-36>Marocco>Ciamis> Christmas. Soluble P increased up to 8 weeks of incubation, and then decreased. The effect of soil mineral ameliorant and some rock phosphates application of soluble P at 12 weeks after the incubation around 15.7-34.2 ppm P. Rock phosphates that has high reactivity gave a high Psolubility on peat soils so it that can be used as P sources in the peat soil.